Mid ureteric stone clearance by Extracorporeal Shock Wave Lithotripsy (ESWL): a clinical study (Journal of Dhaka Medical College, 2015)
Background: In the last 20 years, the management of ureteric stones has changed dramatically from an open operative procedure to endoscopic,minimally invasive and non invasive methods. Urinary stone disease is a major problem due to its high prevalence and incidence and recurrence. The present study aimed to determine the outcome of in situ Extracorporeal Shock-Wave Lithotripsy (ESWL) in mid-ureteric stone in terms of stone clearance, per operative and post operative complications. Methods: This prospective study was conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between September 2011 and August 2012. Total 30 patients with mid ureteric stone sized less than 10 mm were selected purposively. They were evaluated preoperatively by history, physical examination and relevant investigations. ESWL monotherapy with Siemens Lithoscope (3rd generation) lithotripter was used to treat mid ureteric stone. Statistical analysis was done by using SPSS version 13,0. Results: Mean age of the patients was 36.73±8.03 years with a range of 2051 years. Among the patients 18 (60.0%) were male and 12 (40.0%) were female. Seventeen (56.7%) patients had stone in the right ureter and 13(43.3%) had stone in the left ureter. Mean stone size was 8.07±1.32 mm with a range of 6.0010.00 mm. Most of the patients (96.7%) had post procedure pain, 15 (50.0%) had haematuria and 9 (30.0%) had fever. Final outcome of treatment showed that complete stone clearance was 83.3% after one month. Conclusion: Mid ureteric stone clearance with ESWL is more than eighty percent in with a very low rate of complications. So ESWL may be recommended as safe and first line therapy for mid ureteric stones. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21523 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 136-143